Pemberdayaan Kelurahan Dembe Jaya Melalui Pendampingan Keterampilan Deteksi Dini Penyakit Hipertensi - Lusiane Adam; Ahmad Aswad; Rista Apriana; Dirman Abdullah (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2023)
Hypertension is a condition of increasing systolic blood pressure of more than equal to 140 mmHg and diastolic more than equal to 90 mmHg. Hypertension or high blood pressure is a problem found in society, both in developed and developing countries, including Indonesia. Hypertension is one of the number 1 killers in the world and is the cause of 7.5 million deaths. The purpose of this community service is to increase the knowledge and skills of the community in Dembe Jaya Village regarding early detection of hypertension. Dembe Jaya Village was chosen as the location for community service because it is one of the working areas of the North City Public Health Center which has a fairly high number of hypertension sufferers and is an area that has the highest Non-Communicable Diseases. The method of implementing community service is carried out in the form of counselling which is carried out using lecture methods, discussions, consultations, empowerment, mentoring and evaluation of early detection of hypertension and training in using mercury tense meters through a series of activities, namely first licensing, coordination with Dembe Jaya Village and Puskesmas Kota Utara, prepared tools, media for health promotion, and places used for program implementation. As a result of community service, there was an increase in knowledge and skills for early detection of hypertension in Dembe Jaya Village, Kota Utara District, Gorontalo City.